DEVELOPMENT OF THE GREEN ECONOMY IN THE REPUBLIC OF UZBEKISTAN - U. K. Mukhtarova (American Journals, 2025)
Sustainable development is a concept that offers an integrated approach to economic growth, social progress, and environmental protection. It recognizes that economic growth must be sustainable and should not come at the expense of the environment and society. The green economy is one of the key instruments for achieving sustainable development. This article examines the development of the green economy in the Republic of Uzbekistan, analyzes international data on the advancement of energy-saving technologies and the reduction of greenhouse gas emissions, and presents the results of research on modern trends in green financing for implementing projects aimed at introducing resource-saving technologies, creating new capacities through renewable energy sources, and developing socially oriented investment.
Keywords: Green economy, green financing, sustainable development, renewable energy sources, resource-saving technologies, climate change.